2015
DOI: 10.1177/1479164115598274
|View full text |Cite
|
Sign up to set email alerts
|

Association between transcription factor 7-like 2 rs7903146 polymorphism and diabetic retinopathy in type 2 diabetes mellitus: A meta-analysis

Abstract: As one of the vascular complications of type 2 diabetes mellitus, the incidence of diabetes retinopathy is greatly increasing worldwide. Both genetic and environmental factors are involved in the pathologies. A meta-analysis was conducted to assess the association between transcription factor 7-like 2 polymorphism (rs7903146) and type 2 diabetic retinopathy. Published literature from PubMed, Web of Science and China National Knowledge Infrastructure were retrieved. Pooled odds ratios with 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…[49] One of the most important factors is the transcription factor 7-like 2 (TCF7L2), which involves in insulin secretion. [1013] Previous studies have also confirmed that TCF7L2 association is highly reproducible in various ethnic populations with T2DM. [1021]…”
Section: Introductionmentioning
confidence: 85%
“…[49] One of the most important factors is the transcription factor 7-like 2 (TCF7L2), which involves in insulin secretion. [1013] Previous studies have also confirmed that TCF7L2 association is highly reproducible in various ethnic populations with T2DM. [1021]…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies have identified genetic variants significantly associated with DR in various ethnic groups 17 21 . Here, we confirmed the association of PLXDC2, ARHGAP22, CNTN5 , and FMN1 polymorphisms with DR in the Taiwanese population.…”
Section: Discussionmentioning
confidence: 99%
“…All of the genetic markers were selected based on previous reports. The inclusion criteria of candidate SNPs were set as a combined P < 10 −4 for GWAS 18 , 19 , 23 , 29 and a P < 0.05 for meta-analysis 20 , 21 , 30 50 . A total of 58 SNPs in 44 susceptibility loci were evaluated in our study (details are summarized in Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some polymorphisms of the TCF7L2 gene were known to have a role in the development of DR. Ciccacci et al observed that patients with rs12255372 or rs7903146 polymorphisms in TCF7L2 had a more chance for developing DR (73). In a meta-analysis by Ding et al, they found that the rs7903146 (T allele in TCF7L2) was significantly correlated with the elevated risk of DR (P ≤ 0.001) (74). Ma et al reported that Pro12Ala polymorphism of the peroxisome proliferatoractivated receptor γ2 (PPARγ2) gene is another effective polymorphism on the development of DR (75).…”
Section: Genetic Polymorphismsmentioning
confidence: 99%